Project P5: How is assistance in implementing the independent curriculum in elementary schools? - Utaminingsih, Sri; Putri, Jayanti; Rondli, Wawan Shokib; Fathurohman, Irfai; Hariyadi, Ahmad (CV. BImbingan Belajar Assyfa, 2023)
Schools in SD 4 Gulang, Kudus Regency, currently need help in implementing the independent curriculum due to instructors' difficulties in setting themes, selecting sub-themes, determining activities, compiling project modules, and assessing their implementation. This mentoring method consists of seven in-person and online meetings. The results of the assistance demonstrated that SD 4 Gulang was able to modify the project module to strengthen the Pancasila profile of grade 1 students. Project 1's theme and topic were Entrepreneurship and Entrepreneurship Processing Waste, while Project 2's theme was Local Wisdom. My Snacks, My Culture is the topic. Each project's activity phase is divided into the introduction, contextualization, follow-up action, and reflection stages, respectively. Class IV project implementation for Project 1 has the theme of entrepreneurship, with the topic of turning trash into a blessing, and Project 2 has the theme of local knowledge, with the topic of consuming Kudus-style snacks. Strengthening the implementation of the Pancasila Student Profile The project activities at SD 4 Gulang are conducted in accordance with the prepared activity flow, and the assessment is based on the dimensions, elements, and sub-elements that have been determined. Teachers and students' comprehension and proficiency in implementing the Pancasila Student Profile Strengthening increased following mentoring. The Project